Antara Nalar dan Nurani: Konsep Ilmu sebagai Ibadah dalam Tafsir QS Al-Mujadilah:11 - Amalia, Neila; Karomah, Anggeli Navisa; Fadila, Lu`lu Isna; Iskandar, Muhammad Arvi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In Islam, knowledge is not merely the result of rational thinking but an act of worship that elevates human dignity. This concept is reflected in QS Al-Mujadilah:11, which affirms that Allah raises the ranks of those who possess knowledge and faith. This study aims to examine the idea of knowledge as worship through a literature-based approach, referring to classical and contemporary tafsir, as well as the thoughts of Al-Ghazali and Ibn Rusyd. The discussion focuses on the relationship between knowledge, faith, and the order of the universe, along with the understanding of causality in Islamic thought. The findings suggest that knowledge not only explains causal relationships but also leads to a deeper comprehension of God’s will within reality. Thus, scientific activity in Islam integrates both intellectual and spiritual dimensions. This concept is relevant for guiding modern scientific development with divine values.